Scientific and pedagogical activity of the researchers of the Kharkiv Scientific and Pedagogical School (20 – 80s of the 20th century) and their opinions about the pedagogical ideas of H.S. Skovoroda - Sira, I. (New Collegium, 2022)
The article describes the scientific and pedagogical activity of the researchers of the Kharkiv Scientific and Pedagogical School (20-80s of the 20th century) and analyses their opinions regarding the pedagogical ideas of H.S. Skovoroda. The purpose of the article is a theoretical analysis of the scientific and pedagogical activity of the scientists of the Kharkiv Scientific and Pedagogical School based on the pedagogical ideas of H.S. Skovoroda in the 20s-80s of the 20th century. Based on the provisions of the national program “Education (Ukraine of the 21st century)”, pedagogy, in search of ways and means of training higher education teaching staff, turns to the study and use of the heritage of domestic educationalists. This approach will contribute to the discovery of their theoretical ideas and experience, will allow to add new materials to the history of pedagogical thought of Ukraine, will help to reveal the possibilities of creative use of the acquired general pedagogical experience in modern higher educational institutions. Since the beginning of the 1920s, Ukraine has undergone significant changes in the development of pedagogical thought. The process of Ukrainization of education and science was underway, national culture, art, and literature were developing. The Ukrainian language began to be widely used in teaching and education, the foundations of a new system of public education as a whole and higher pedagogical education as its important component were laid. The article contains short biographies and characteristics of the pedagogical activity of such educationalists as: S.A. Litvinov, M.O. Hryhoriev, A.I. Zilberstein, I.T. Fedorenko, who studied the theory and history of pedagogy, focusing on the development of didactics. It was noted that the deep interest of the scientists of the Kharkiv Scientific and Pedagogical School of the professors of the Kharkiv Pedagogical Institute named after H.S. Skovoroda (M.O. Hryhoryev, A.I. Zilbershtein, S.A. Lytvynov, I.T. Fedorenko) through the views of the humanist teacher Hryhoriy Skovoroda led to the study and generalization of his pedagogical heritage. It was determined that when studying the works of H.S. Skovoroda, scientists highly appreciated the poet’s attitude to the process of education and upbringing based on humanism. It has been proven that the scientists of the Kharkiv Scientific and Pedagogical School believed that the pedagogical ideas of H.S. Skovoroda left a deep mark in the history of pedagogical thought.